2017
DOI: 10.5812/whb.13241
|View full text |Cite
|
Sign up to set email alerts
|

Causal Model for Depression Based on Psychological Capital by Mediating of Hospital Stress and Anxiety in Woman Nurses

Abstract: Background: In modern societies, nurses' issues and investigation of their problems has found a vital importance. Objectives: The present study investigated the mediating role of hospital stress and anxiety in relationship between psychological capital and depression in women nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
1
Order By: Relevance
“…Besides, results of a study by Faramarzi and Khafri (2017) which showed no significant correlation between symptoms of anxiety or depression and selfefficacy. However, it contradicts the research by Baezzat, et al (2017) which did find that the self-efficacy dimension affects an individual's anxiety and depression. In addition, Selvaraj and Bhat (2018) found that the higher the levels of optimism, self-efficacy and hope among college students, the more likely they are to enjoy positive mental health.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Besides, results of a study by Faramarzi and Khafri (2017) which showed no significant correlation between symptoms of anxiety or depression and selfefficacy. However, it contradicts the research by Baezzat, et al (2017) which did find that the self-efficacy dimension affects an individual's anxiety and depression. In addition, Selvaraj and Bhat (2018) found that the higher the levels of optimism, self-efficacy and hope among college students, the more likely they are to enjoy positive mental health.…”
Section: Discussioncontrasting
confidence: 75%
“…A study by Baezzat, et al (2017) showed that the dimensions of psychological capital have a significant relationship with anxiety and depression. This study, however, found that only three dimensions of psychological capital -hope, resilience and optimism -are negatively correlated with anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%